In situ and real-time monitoring of intracellular activities in single live cells using a nanopore probe - Xiaobin Huang; Ziyi Li; Yanling Huang; Ke Zhou; Lei Liu; Hai-Chen Wu (Proceedings of the National Academy of Sciences, 2026)
Monitoring molecular activities within single live cells is vital for understanding cellular differentiation, senescence, heterogeneity, and disease progression. However, conventional single-cell analyses often rely on micromanipulation or extraction followed by downstream measurements, which cannot capture in situ real-time dynamics. Fluorescent labeling and electrochemical methods provide temporal resolution but face limitations in labeling, substrate scope, and multiplexing. Here, we present a nanopore probe that enables real-time, multiplexed monitoring of intracellular activities in single live cells. The device integrates an aluminum oxide nanostraw membrane for molecular extraction and a glass nanopore membrane for single-channel electrical detection. Using a hippocampal neuron model of ischemia-hypoxia, we simultaneously tracked dynamic changes in intracellular glutamate, ascorbic acid, and adenosine triphosphate—three key molecules involved in oxygen-glucose deprivation-induced neuronal edema. Our findings establish this nanopore probe as a powerful platform for real-time, label-free molecular profiling at the single-cell level, opening opportunities for studying disease mechanisms and therapeutic responses.